Predstavitev avtorja v čeških in slovaških znanstvenih besedilih - Čmejrková, Světla (Jezik in slovstvo, 2007)
This paper poses the question of how academic writers present themselves to the audience and focuses on the functions of forms of self-reference in Czech and Slovak scientific discourse. For scientific texts, the Latin rhetoric tradition recommended the so called pluralis modestiae or pluralis auctoris asan appropriate linguistic means of self-presentation of the writer, conveying his modest and non-imposing approach to the reader. Whereas in the English academic setting this habit has been abandoned in favor of the more responsible "I" presentation, writers of Slavic linguistic and cultural background still adhere to the "we" textual self. The paper focuses on the function of the we-perspective in Czech and Slovak scientific texts and distinguishes between their ideational, interactional and textual functions.
Keywords: češčina; slovaščina; znanstveni jezik; retorika; rhetoric; avtorstvo; tekstna lingvistika